Optimum design of timber structures under fire using metaheuristic algorithm - Serdar Ulusoy (Građevinar)
One of the major tasks of structural engineers is to reduce the building cost. Thus, an effective optimization of structural elements is gaining in importance every day. The teaching-learning-based optimization (TLBO), which is one of metaheuristic algorithms, for an optimum design and analysis of timber structures under fire in accordance with EN 1995 1-2 (Eurocode 5: Design of Timber structures - Part 1- 2 General structural fire design), is proposed in this study. The objective function in this algorithm is the building cost of timber structures under fire, considering premature collapse of the structure and limitation of fire spread. A structure made of wood is investigated under different times of fire exposure in order to determine the cross-section and wood type of structural elements. In conclusion, the cross section and strength of structural elements made of wood can be effectively and rapidly optimized with TLBO according to EN 1995 1-2.